2015
DOI: 10.1007/s12237-015-9978-7
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Blue Crab (Callinectes sapidus) Megalopae at the Mouths of Chesapeake and Delaware Bays: Implications for Larval Ingress

Abstract: Transport of Callinectes sapidus (blue crab) megalopae from the continental shelf into estuaries may influence recruitment variability of this species. Observations of the vertical distribution of C. sapidus megalopae near the mouths of Chesapeake and Delaware Bays were used to infer vertical swimming behaviors that may influence ingress to these estuaries. Megalopae and oceanographic conditions were sampled at locations from~10 km inshore of the estuary mouths to~40 km offshore in coastal shelf waters on Sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Megalopae reenter estuaries and settle in nursery habitats containing submerged aquatic vegetation (Perry et al 2003, Spitzer et al 2003. Blue crab larvae display distinct patterns of vertical distribution in the water column throughout ontogeny (Epifanio 1988, Biermann et al 2016). Sulkin et al (1980) studied the behavior of blue crabs under laboratory conditions and found that early zoeae I occurred high in the water column and late zoeae IV-VII occurred in deeper vertical positions, suggesting a daily vertical migratory (DVM) behavior.…”
Section: Blue Crab Life Historymentioning
confidence: 99%
See 2 more Smart Citations
“…Megalopae reenter estuaries and settle in nursery habitats containing submerged aquatic vegetation (Perry et al 2003, Spitzer et al 2003. Blue crab larvae display distinct patterns of vertical distribution in the water column throughout ontogeny (Epifanio 1988, Biermann et al 2016). Sulkin et al (1980) studied the behavior of blue crabs under laboratory conditions and found that early zoeae I occurred high in the water column and late zoeae IV-VII occurred in deeper vertical positions, suggesting a daily vertical migratory (DVM) behavior.…”
Section: Blue Crab Life Historymentioning
confidence: 99%
“…However, field observations did not coincide with these findings because zoeae have been found near the surface throughout all development stages (Epifanio et al 1984, Epifanio 1988, Little & Epifanio 1991. On the other hand, a DVM behavior for megalopae was observed by Epifanio et al (1984) and Biermann et al (2016). Near the estuaries, megalopae perform vertical migrations synchronized with the flood phase of the tide to complete their ontogenetic migrations between oceanic and estuarine habitats, a mechanism known as selective tidal stream transport (STST) (see Forward & Tankersley 2001 for review).…”
Section: Blue Crab Life Historymentioning
confidence: 99%
See 1 more Smart Citation
“…have documented a diel pattern in activity suggesting transport is reliant on wind forcing and density driven flows into Delaware Bay (Biermann, North, & Boicourt, 2016). Previous studies on menhaden suggest larvae engage in diel migratory behavior (e.g., Forward, Tankersley, & Burke, 1996;Forward et al, 1999;Hoss, Checkley, & Settle, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…These thresholds determined in the present study should not be viewed as definitive because they depend on the stimulus resolution used in behavioral experiments, which was purposefully kept at half-log steps to limit light exposure of dark-adapted larvae. Nevertheless, the relative difference observed between photoresponse thresholds for Z3 stage larvae (5.8 × 10 12 photons m − 2 s − 1 ) and Z5 stage larvae (1.2 × 10 14 photons m − 2 s − 1 ) would result in later-stage larvae residing~10 m shallower during the daytime than earlier-stage larvae given optical properties of the Delaware Coastal Current (e.g., Biermann, 2009). A shallower daytime vertical distribution of Z5 stage H. sanguineus larvae, the depth of which is set by the lower visual threshold (Sulkin, 1984), would lead to even greater transport northward toward source populations by upwelling wind-driven surface currents than for deeper-dwelling Z3 stage larvae.…”
Section: Discussionmentioning
confidence: 99%